No Participant Left Behind: Conducting Science During COVID-19 - Lourenco, Stella F. (Trends Cogn Sci, 2020)
Cognitive scientists have ramped up online testing in response to the COVID-19 pandemic. Although research conducted online solves the problem of data collection, the paucity of internet access among low-income and minority communities may reduce the diversity of study samples, and thus have an impact on the generalizability of scientific findings.